Determinants of Consumer Purchase Decisions at Ant Accessories: The Role of Product Diversity, Price, and Service Quality - Cinta Setyo Utami; Helman Fachri (Universitas Muhammadiyah Pontianak, 2026)
This study examines how product assortment, price, and service quality jointly and individually shape consumer purchase decisions in a small fashion-accessories retailer in Pontianak, Indonesia. Using an explanatory quantitative design, data was collected through structured questionnaires from 100 customers selected by purposive sampling and analysed with multiple linear regression. All three predictors exert a positive and significant effect and together explain 49.5 per cent of the variance in purchase decisions (F = 31.317; p < 0.001). Price carries the largest standardised effect, followed by service quality and product assortment. The findings extend assortment and service-quality research to resource-constrained SME retailing in an emerging market. Keywords: Product Assortment; Price; Service Quality; Purchase Decision; Retail Marketing; Consumer Behaviour; SME Retailing